Template‐Electrodeposited Plasmonic Metasurfaces for High‐Sensitivity Biomolecular Detection (Adv. Mater. Interfaces 17/2022). Issue 17 (14th June 2022) - Li, Guohua; Wu, Mingxi; Ye, Xiangyi; Zhou, Jianhua; Cai, Jingxuan
Abstract : Plasmonic Metasurfaces A high‐throughput, cost‐effective, and scalable nanofabrication method based on templated electrodeposition for fabricating deterministic metallic nanostructures is reported in article number 2200292 by Guohua Li, Jianhua Zhou, Jingxuan Cai, and co‐workers. The electrodeposition template could be reused more than ten times, and the performance of successive plasmonic metasurfaces fabricated using the same template is highly consistent. This nanofabrication process is a promising technique for mass‐fabrication of deterministic metallic nanostructures.